Urine methamphetamine-to-amphetamine ratio by LC-MS/MS to differentiate methamphetamine use from pharmaceutical impurity in patients prescribed amphetamine - Lindsey Contella; Phillip Kang; Clara E. Wolf; Victoria L. Thomas; Melissa Gildenberg; Marion L. Snyder; Stacy E.F. Melanson; Nicole V. Tolan (Journal of Mass Spectrometry and Advances in the Clinical Lab)
Introduction: Patients compliant with prescribed amphetamine (AMPH) should not have detectable methamphetamine (METH) in their urine; detectable METH typically indicates illicit use. However, we have identified patients with results suggestive of METH as an impurity in prescribed AMPH. Objectives: Derive a METH:AMPH ratio cut-off from a training set of patients compliant with AMPH prescriptions to differentiate METH as an impurity from illicit use. Methods: Retrospective review of AMPH and METH-positive cases by liquid chromatography-tandem mass spectrometry (LC-MS/MS) at Brigham and Women’s Hospital (BWH) and Luxor Scientific. Correlated results with clinical and medication history and compliance with prescribed medications. Results: The median ± interquartile range (IQR) METH:AMPH ratio for the Adderall training sets was 0.43 ± 0.31 % and 0.05 ± 0.040 %, with a maximum ratio of 1.125 % and 0.125 % at BWH and Luxor, respectively. The median ± IQR METH:AMPH ratio for the Luxor d-AMPH training set was 0.039 ± 0.028 %, with a maximum ratio of 0.09 %; not statistically different from the Adderall training set. Assessment of the BWH test set where METH < AMPH (n = 22) revealed that METH was likely due to an impurity (n = 10), distant METH mis/use (n = 11), or requiring further analysis (n = 1). METH was also detected by LC-MS/MS in a commercial AMPH calibrator and in Adderall XR. Discussion: METH may represent an impurity in the AMPH formulation. Laboratories are encouraged to define a METH:AMPH ratio below which an impurity is the likely explanation for METH and/or to increase the METH positivity cut-off to 50 or 100 ng/mL to reduce potential false-accusations of illicit METH use.